An Analysis the Factors of Students’ Difficulties in Speaking English Faced by non-English Department Students - Vini Gusviyani; Naf’an Tarihoran; Busthomi Ibrahim (English Education, Linguistics, and Literature Journal, 2022)
Abstract: The purpose of this research is to find out The Factors of Students’ Difficulties in Speaking English Faced by non-English Department Students. This research was conducted with qualitative research, with using survey method. This research used google form as questionnaire to gain the data. The respondents of this research are the 100 students of non-English department at Faculty of Education UIN SMH Banten. The result of this research showed that there were many factors that students have in English speaking difficulties. They are factor anxiety does not master the vocabulary has value 59% agreed, then factor shy of being an intention has value 57% agreed, then factor lack of confident has value 54% agreed, factor lack of self motivation has value 54% agreed, factor of environmental effect has value 54% agreed, factor there is no preparation has value 53% agreed, then factor fear of wrong pronouncing has value 52% agreed, factor of fear of use the wrong words has value 49% agreed, factor affective of students has value 48% agreed, and the last factor anxiety of being bullied has value 44% agreed. It means students have some factors in speaking problem that should be take more attention.